"Raising the curtain on the equality theatre": a study of recruitment to first healthcare job post-qualification in the UK National Health Service - John Hammond; Nigel Davies; Elizabeth Morrow; Fiona Ross; Tushna Vandrevala; Ruth Harris (BMC, 2022)
Abstract Background UK equality law and National Health Service (NHS) policy requires racial equality in job appointments and career opportunities. However, recent national workforce race equality standard (WRES) data show that nearly all NHS organisations in the UK are failing to appoint ethnically diverse candidates with equivalent training and qualifications as their white counterparts. This is problematic because workforce diversity is associated with improved patient outcomes and other benefits for staff and organisations. Aim To better understand the reasons behind underrepresentation of ethnically diverse candidates in first NHS healthcare jobs post-qualification and to identify any structural or systemic barriers to employment for such groups. Methods The study was informed by critical theory and the authors' interdisciplinary perspectives as educators and researchers in the healthcare professions. Data collected from semi-structured face-to-face interviews with 12 nurse and physiotherapy recruiting managers from two NHS trusts in London were analysed using a healthcare workforce equity and diversity conceptual lens we developed from the literature. Using this lens, we devised questions to examine six dimensions of equity and diversity in the interview data from recruiting managers. Results Recruiting managers said they valued the benefits of an ethnically diverse workforce for patients and their unit/organisation. However, their adherence to organisational policies for recruitment and selection, which emphasise objectivity and standardisation, acted as constraints to recognising ethnicity as an important issue in recruitment and workforce diversity. Some recruiting managers sense that there are barriers for ethnically diverse candidates but lacked information about workforce diversity, systems for monitoring recruitment, or ways to engage with staff or candidates to talk about these issues. Without this information there was no apparent problem or reason to try alternative approaches. Conclusion These accounts from 12 recruiting managers give a 'backstage' view into the reasons behind ethnic inequalities in recruitment to first healthcare job in the UK NHS. Adherence to recruitment and selection policies, which aim to support equality through standardisation and anonymisation, appear to be limiting workforce diversity and creating barriers for ethnically diverse candidates to attain the jobs that they are trained and qualified for. The Healthcare Workforce Equity + Diversity Lens we have developed can help to 'raise the curtain on the equality theatre' and inform more inclusive approaches to recruitment such as contextualised recruitment or effective allyship between employers and universities.